Metodologia de leitura e análise dimensional aplicada no estudo das faces de 15 esculturas de Antônio Francisco Lisboa, mestre Aleijadinho - Lucienne Maria de Almeida Elias (2015)
This study aims to characterize the "handwriting" sculpture of Antonio Francisco Lisboa, Master Aleijadinho, through reading and dimensional analysis of the elements comprising the faces of 15 devotional sculptures. This method allows establishing and determining the metric relations of the sculpted forms, as well as constants and variables existing standards. The case study authentic works, e.g. deals with at the Christ of the Last Supper, Christ Garden, Christ Prison, Christ of the Flagellation, Christ of the Green Cane, Christ of the Cross-on-the-back, Christ Crucifixion, dating from the third phase of the sculptor and belonging to the group of sculptures of the Stations of the Cross of Our Sanctuary Senhor Bom Jesus de Matosinhos, sculptures of St. Simon Stock and John of the Cross, belonging to the Church of Our Lady of Mount Carmel of Sabara, the second Master Aleijadinho phase and a group of six Reliquary Busts who are exposed in the Basilica of Senhor Bom Jesus de Matosinhos in Congonhas, representing St. Ambrose, St. Augustine, St. Jerome, St. Gregory (3a sculptor's production), St. Basil and St. Nicholas , dating from the first phase of the sculptor. The theoretical framework is based on the representation of the human body along the History of Art, designed the various canons and its peculiarities. In addition, we are used interdisciplinary tools from the Humanities, Natural Sciences and Exact Sciences, gathering information from biometric and anthropometric studies of the human body, numerical ratios and mathematical proportions, elements of design, Metrology, of Biostatistics and Statistics. The analysis of the body of work includes the mapping of elementary variables for data collection, data processing, comparing information collected through Cluster Analysis and also PCA -Principal Component Analysis. At the end, found at the describe the relations we analyzed set of data, the standardized variables and conclusive dimensional model of the technical and creative process of master Aleijadinho.